Limited Scale of the Face-to-Face Learning Analyze to Student Learning Saturation for the First Grade (X Class) of Senior High School in Biology Lesson - Siregar, Fatimah Zahara; Ulfa, Syarifah Widya (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
This study aims to determine the level of student learning when face-to-face learning is limited to biology subjects at Senior High School of SMA Negeri 1 Batang Kuis and the factors that influence it. The research method uses qualitative methods. The research population includes three classes, namely X MIA Class with a sample of 35 students, namely X MIA1 Class and X MIA2 Class as many as 34 students and X MIA 3 Class as many as 31 students. Research data in the form of biology teacher interviews and student questionnaires were developed according to indicators of learning saturation, namely emotional exhaustion, physical exhaustion, cognitive fatigue, and loss of motivation. The data collected was processed using a Likert scale technique, which was measured and translated into variable indicators. The data analysis technique uses the Miles & Huberman model, which consists of 3 stages, namely data reduction, data presentation, as well as inference and validation. The results of this study show that during face-to-face learning the scale is limited to the indicator of emotional exhaustion of the dominant student in the saturated category, on the indicator of physical fatigue the dominant student is in the saturated category, on the indicator of cognitive fatigue the dominant student is in the saturated category, on the indicator of loss of motivation The dominant student is in the very saturated category